Tourist satisfaction towards safety and security in Melaka / Yasmin Mohd Yusoff and Hasydan Razali - Mohd Yusoff, Yasmin; Razali, Hasydan (Faculty of Hotel and Tourism Management, 2013)
This research is conducted to determine the satisfaction level of tourist or visitor that visit Melaka. The determinants will be measured by looking at the safety and security factor. The local and international tourist perspectives towards safety and security will be discussed, and this will include the strategies which should be develop in order to improve safety and security in Melaka, and in the same time to increase the level of tourist satisfaction. Primary data and secondary data were collected accordingly. A set of questionnaire had been distributed to local and international tourists who were easily located in attraction places in Melaka. The finding will be the major different among the local and international tourist who come to visit Melaka in different time frame which is day and night. Their satisfaction level towards safety and security in Melaka had shown the differences. Somehow, there were still some factor that most of them think contribute in their decision in choosing Melaka as a destination to visit, such as the history of Melaka and the stability of the country, Malaysia. Recommendation to the Melaka state will include the suitable strategies and tools which the researchers find to be relevant in order to increase the level of satisfaction and to attract more local and international tourists to Melaka. Besides, improvements of some facilities were needed by looking at some of the comment given by respondents.